The challenges facing the Arabic language in the digital era – the lexical gap as a model - Mabdoua, Karima (El Omda in Linguistics and Discourse Analysis, 2024)
Abstract: This research paper addresses the most important problems facing the Arabic language today in light of digitization, the absence of policies of interest in developing it, financing its scientific research, keeping pace with technology, and the weakness of the translation movement at the expense of the sovereignty of foreign languages. It will have its main role in the global cultural and cognitive movement, and finding effective solutions to develop and spread it in the world as a whole in a correct and systematic way that allows spreading the teachings of religion and the culture of the Arab nation and its ancient history, as well as by overcoming the reality of the state of the Arabic language, which is experiencing a crisis on many levels, because this language It possesses the elements and characteristics that make it able to keep pace with scientific and technical developments and their cognitive results.